Perforated Appendicitis Treated By Open Versus Laparoscopic Surgery- A Comparative Study - Timilsina, Bishow Deep; Karki, Om; Subedi, Babita (Nepal Mediciti Medical Journal, 2021)
Background: Acute appendicitis is the most common surgical emergency of the abdomen. Perforated appendicitis often has higher morbidity and mortality. Laparoscopic Appendectomy (LA) is safe and effective procedure for the simple appendicitis compared to Open Appendectomy (OA) but it is not considered as the first line approach in case of perforated appendicitis and its role is still controversial and is under investigation. Hence this study was carried out to compare the outcomes of LA over OA in proven cases of perforated appendicitis.Methods: A hospital based comparative study was conducted among 60 patients with the diagnosis of perforated appendicitis who underwent LA and OA, for a duration of 18 months in Manipal Teaching Hospital, Pokhara. Data were collected using semi-structured questionnaire and were analyzed by descriptive and inferential statistics with SPSS version 25.0.Results: The study showed no significant statistical difference in operative time in LA compared to OA (66±18.11 minutes vs. 66.67±25.269 minutes, p = 0.9). Moreover it shows less post-operative pain (p = 0.003), shorter length of hospital stay (5.3±1.8 days vs. 7.3±3.31 days, p = 0.005), faster return of peristalsis (1.43±0.504 days vs 1.80±0.805 days, p = 0.037) and faster reinstitution of liquid diet(1.43±0.504 days vs 1.80±0.805 days, p = 0.037), less incidence of wound infection (5 in 30 = 16.66% vs. 12 in 30 = 40%, p = 0.042) and faster subjective full recovery(1.9±0.759 weeks vs. 2.9±0.89 weeks, p ˂ 0.0001) of LA patient compared to OA which is statistically significant.Conclusion: LA is safe and effective procedure than OA for perforated appendicitis.